Effect of Textual Integrity of Argumentative Texts on EFL Learners’ Reading Performance: Different Levels of Language Proficiency in Focus - Lavenezhad, Mona; Vahid Dastjerdi, Hossein (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
The present study aimed at investigating the effect of textual integrity of argumentative texts on EFL learners’ reading comprehension performance. It also aimed at checking the extent of such an effect among learners with different language proficiency. To this purpose, 120 students learning English at Jihad Daneshgahi Institute in Isfahan were selected as the participants. They were selected from a pool of 200 available and interested students and were divided into three groups of low proficient, intermediate and high proficient learners of equal size (40), based on their scores on an OQPT proficiency test. Then, 3 reading comprehension tests (cloze tests), with an appropriate level of text difficulty, were prepared by the researcher. In making the tests, the text in each test was either kept authentic in terms of textual integrity (i.e. text organization, cohesive devices, etc.), or manipulated to lose its textual unity and, thus, be more difficult to read and understand. The results of data analysis indicated that manipulated argumentative texts negatively affect EFL learners’ reading performance at all levels of language proficiency. The results additionally revealed that text manipulation, i.e. textual integrity decrease, has a more significant effect on the reading performance of the intermediate group participants. The findings of this study can have some implications for language teachers to become more alert to the effect of textual integrity of texts on reading comprehension performance of students when trying to understand argumentative texts. Furthermore, the findings might be constructive for materials developers, i.e helping them to prepare appropriate texts in terms of textual integrity and readability, in line with the needs and levels of EFL learners.